Recent and future innovations in the treatment of heart failure [Kalp yetersizliǧi tedavisinde yeni açılımlar: Şimdi ve gelecek] - KEPEZ, ALPER; MUTLU, BÜLENT (AVES, 2013)
Heart failure is still an important public health problem despite important advances regarding its treatment. Several new treatment strategies are being investigated in order to contend with this disease. Strategies proved to be safe and effective in clinical trials are being adapted to clinical practice. In this review, we will first focus on most recent treatment strategies that are recommended to be used in clinical practice and then try to mention novel strategies which are still being explored in preclinical studies. © 2013 by AVES Yayincilik Ltd.
Keywords: Clinical trials; Guidelines; Heart failure